Potential Roles of Exosomal lncRNAs in the Intestinal Mucosal Immune Barrier. (26th August 2021) - Chen, Shanshan; He, Ruonan; He, Beihui; Xu, Li; Zhang, Shuo
Abstract : The intestinal mucosal immune barrier protects the host from the invasion of foreign pathogenic microorganisms. Immune cells and cytokines in the intestinal mucosa maintain local and systemic homeostasis by participating in natural and adaptive immunity. Deficiency of the intestinal mucosal immune barrier is associated with a variety of intestinal illnesses. Exosomes are phospholipid bilayer nanovesicles that allow cell-cell communication by secreting physiologically active substances including proteins, lipids, transcription factors, mRNAs, micro-RNAs (miRNAs), and long noncoding RNAs (lncRNAs). Exosomal lncRNAs are involved in immune cell differentiation and the modulation of the immune response. This review briefly introduces the potential role of exosomal lncRNAs in the intestinal mucosal immune barrier and discusses their relevance to intestinal illnesses.